Toxicology, environmental chemistry, ecotoxicology, and One Health: definitions and paths for future research - Sauvé, Sébastien (Frontiers in Environmental Science, 2024)
The definitions of toxicology, environmental toxicology, environmental chemistry, environmental risk and ecotoxicology are closely related and sometimes used as synonyms whereas One Health is a more recent, complementary concept. This contribution examines the origins of the usages of these terms, their interchangeability (whether appropriate or not) and proposes some paths to better define each. The usage of these terms is evolving, and current research and paradigm are progressing towards the integration of broader, more integrative perspectives such as the One Health approach. One Health is a holistic approach that help to link and integrate work on environmental and human health impacts. Definitions and research should not necessarily strive to segregate human vs environmentally focused work and most of the problems are complex and interconnected. Future research endeavors and funding programs must better reflect the multidisciplinary nature of environmental toxicology and more broadly, One Health research and environmental research must recognize the interrelationships of human health, environmental health, ecotoxicology and a multitude of geochemical, microbiological and ecological processes.